Pengaruh Tekanan Pemegang Saham dan Umur Perusahaan terhadap Kualitas Sustainability Report - Willy Sri Yuliandhari; Ardan Gani Asalam; Muhammad Visar Sinatrya (Owner : Riset dan Jurnal Akuntansi, 2023)
Sustainability report is a report submitted to the company's stakeholders to report the impact of company's activities on environment, social, and economy. Companies are expected to submit quality information to demonstrate corporate responsibility and can be used as a consideration in making decisions. However, there are still many companies that have not submitted a good and quality information in sustainability report. This study aims to determine the effect of shareholder pressure and company age on sustainability report quality. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses purposive sampling technique. Based on the sampling technique and criteria, 11 companies were obtained with an observation period of three years, so the total observations are 33 samples. This study uses descriptive statistical analysis methods and panel data regression models using Eviews 12 SV software. The results of this study indicates that the age of the company has a significant positive effect on sustainability report quality. Meanwhile, shareholders pressure do not affect the sustainability report quality. Based on the results of this study, the company is expected to improve the quality of the sustainability report in accordance with the GRI Standards and investors are expected to make the sustainability report as one of the considerations in investing. Future researchers are expected to use other independent variables or use different proxies for the variables and are also expected to choose a different research object.